O jeito nordestino de ser globalizado - Nepomuceno, Cristiane Maria (2005)
This work discusses the impacts of the globalization in the Brazilian northeast culture, specifically in the popular field. The background of theses reflections is the carnival festivities in Recife-PE. In this context, attempts to changes as well as resistance to them maintaining the cultural values and the popular manifestations take a new dimension, presenting different ways of being nordestino. The option for the context of the carnival festivities is due to its significance to the people of this place, particularly as it is a space in which people represent themselves. The work presents a version of the history of carnival in Recife, identifies some manifestations that comprise it, analyzes its changes and shows the process of valuing the local culture in the latest years of the 20th century. The research also reveals how the popular culture assumes a functional and dynamic character where the themes of the popular traditions are being reworked. This process allows not only the survival of the local culture, but also the resistance against the capitalist project to construct a global culture and its uniform character. Even though the carnival festivity has become a mega show, composing a market design, it is still a space to construct differences and see the other. Lastly, for the people of that region, it is a space of fighting for a place in the international panorama